Mutagenesis associated with nitric oxide production in macrophages - Zhuang, John C. (The National Academy of Sciences, 1998)
To better understand the mechanisms through which persistent infections/inflammation increase cancer risks, we assessed the potential genotoxic properties of NO produced by macrophages. We recently showed that mouse macrophage RAW264.7 cells were capable of resuming exponential growth after stimulation for NO production by interferon-γ (IFN-γ) and/or lipopolysaccharide. Here, we report that increases in mutant fraction (MF) in the endogenous, X-linked, hprt gene of the cells are associated with NO exposure. Cells stimulated with 100 units/ml IFN-γ continuously for 14 and 23 days produced a total of 9.8 and 14 μmol of NO per 10(7) cells, respectively. MFs in the hprt gene of NO-producing cells were 16.6 and 31.3 × 10(−5), respectively, compared with 2.2 and 2.5 × 10(−5) in untreated cells. Addition of an NO synthase inhibitor, N-monomethyl-l-arginine, to the culture medium decreased NO production and MF by 90% and 85%, respectively. Reverse transcription-PCR and DNA sequencing revealed that NO-associated hprt mutations did not differ significantly from those arising spontaneously, with the exception that certain small deletions/insertions and multiple exon deletions were observed only in the former. MF also increased significantly in cells stimulated for only 4 days with lipopolysaccharide plus IFN-γ for higher rates of NO production. The types and proportion of hprt mutations induced under these conditions were strikingly similar to those associated with long-term NO exposure. These results indicate that NO exposure results in gene mutations in RAW264.7 cells through mechanisms yet to be identified and may also contribute to spontaneous mutagenesis.